Multi-Objective Awareness Schemes for Virtual Machine Placement in Cloud Computing using Reinforced Evolutionary Algorithm - Shanmugam, Veeramani (Curtin University, 2023)
In this research, the Virtual Machine Placement (VMP) problem in Cloud Computing environment have been solved effectively using a Multi-Objective Enhanced Discrete Butterfly Optimization Algorithm by considering Network, Communication, and Thermal-aware based objectives for placing virtual machines on cloud servers. The proposed algorithms are tested under standard performance metrics. The experimental results show that the proposed algorithms outperform existing evolutionary algorithms, and this encourages further investigations in the field of VMP in Cloud Computing.